Importance of Ayer Hitam Forest Reserve in the Klang Valley and the Multimedia Super Corridor - Lim, Meng Tsai; Yaacob, Tunku M. Nazim; Jeyaraj, Kishokumar (Universiti Putra Malaysia Press, 2001)
The location of the Air Hitam Forest Reserve within the Klang Valley and the Multimedia Super Corridor is highlighted and compared to the state and extent of other forested areas in the Klang Valley and the Multimedia Super Corridor. As insufficient detailed information was available the estimates for the all forested area were based on the forest resources map (FS6 from 1991). Population of the areas were also estimated from the 1990 census. Some projections to the respective conditions in 2000 was also made and discussed.